Measurements of OH* and CH* in a constant volume combustion bomb - Hu, M (2013)
Combustion monitoring in internal combustion engine or burners is a difficult task due to the harsh environment for any sensor, therefore optical diagnostics are very attractive for these types of application. Chemiluminescence measurement is one of the most common and most promising ways of implementing optical diagnostics in combustion monitoring applications because the measured signal, emitted naturally with combustion, has potential to be an indirect measure of combustion relevant parameters, such as the equivalence ratio and heat release rate. In hydrocarbon combustion, the most common chemiluminescence emitters are OH*, CH*, C2* and CO2*. This thesis focuses on the measurement of OH* and CH* chemiluminescence, whose sensitivities are affected by temperature, pressure, equivalence ratio and stretch rate. To measure OH* and CH* chemiluminescence, an existing constant volume combustion vessel has been refurbished, along with the sub-systems for fuel delivery, ignition, LabView control, data acquisition, and optical detection using a pair of photo-multiplier tubes (PMTs), interference filters and a series of apertures. Modelling accurately the optical setup is essential for the CH* and OH* chemiluminescence measurements in the combustion bomb. To achieve this goal, a narrow field of view system has been selected as it enables the elimination of photons scattered from the internal surfaces. A calibration of the PMTs converts the measurements into the absolute OH* and CH* chemiluminescence in terms of watt. Measurements from a combustion bomb are versatile and accurate since it determines the OH* and CH* chemiluminescence as a function of temperature and pressure from a single experiment. The calculation of the normalised OH* and CH* chemiluminescence (against mass burned rate) was based on a multi-zone combustion model and measured pressure record from the vessel. NIICS (Normalised Intensity Integrated Calculation System) has been created to fetch data from the multi-zone model, the optical model, and experimental measurements, to match them up by interpolation and to normalise the OH* and CH* chemiluminescence. NIICS also allows the user to select data uncorrupted by the noise and heat transfer. The chosen data (in this case, CH*/OH* chemiluminescence ratio) have been fitted using a multi-variate fitting and correlation analysis. This formulation can be used to indicate the local equivalence ratio from premixed methane / air and iso-octane / air flames over the local pressure range 0.5 – 20 bar, the unburned gas temperature range 450 – 600 K, and equivalence ratio range 0.8 – 1.1. The chemical-kinetic mechanisms of the absolute OH* and CH* chemiluminescence have been investigated by studying the influence of the equivalence ratio, unburned gas temperature, and local pressure. It should be pointed out that two confounding observations occur, i.e. a discontinuity in the chemiluminescence along the isentropes, and chemiluminescence continuing after the end of combustion. This led to the further spectroscopic analysis. This study concluded with spectroscopic measurements using an Ocean Optics spectrometer and a Princeton ICCD spectrometer. It was found that the broadband CO2* is responsible for the two disconcerting observations. In addition, CH* chemiluminescence has been shown to be very faint from premixed laminar methane / air flames; hence the CH*/OH* formula in essence quantifies the CO2*/OH* ratio as a function of pressure, temperature, and equivalence ratio. The ‘CH* chemiluminescence’ can characterise the background CO2*, so as to provide a practical way to probe the feasibility of absolute OH* as an indicator of combustion relevant parameters in the future.